IMPROVING ABILITY TO KNOW THE CONCEPT OF NUMBER THROUGH COUNTING ACTIVITIES USING MEDIA BOTTLE CAP FOR CHILDREN IN GROUP B-2 KINDERGARTEN NEW CITY EMPLOYEES - Rosmawar Rosmawar; Ahmad Nasriadi; Fitriah Hayati (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The ability to recognize the concept of numbers needs to be introduced from an early age, where at an early stage, children must first be introduced to simple number concepts. This study aims to determine the increased ability to recognize numbers through counting activities using bottle caps in children in group B-2 Kindergarten Employees of Kota Baru. This study uses a classroom action research design by adopting the Kemmis and MC Taggart models with four action stages: planning, implementation/action, observation, and reflection. The number of subjects is 20 children; data collection is done through observation and documentation. The results showed that there was an increase in numeracy skills through the media of bottle caps in children in group B-2 Kindergarten Employees, namely the pre-cycle results only developed 20%, increased to 55% in cycle I, in cycle II increased to 85% while exceeding the standard of participant development students set at 80%. The teacher's activity in learning to count using bottle cap media in cycle I was categorized as good with a score of 77.25%, increasing to very good in cycle II with a score of 98.25%. Children's activity in learning to count using bottle cap media in cycle I was categorized as sufficient with a score of 64%, increasing to very good in cycle II with a score of 88.25%. This study concluded that counting activities using bottle cap media can improve the ability to recognize the concept of numbers in kindergarten children.